A systematic review and meta-analysis of PD-1/PD-L1 inhibitors in specific patient subgroups with advanced gastro-oesophageal junction and gastric adenocarcinoma. (January 2021) - Formica, V.; Morelli, C.; Patrikidou, A.; Shiu, KK.; Nardecchia, A.; Lucchetti, J.; Roselli, M.; Arkenau, HT.
Graphical abstract: Highlights: Immune checkpoint inhibitors have shown contradictory results in patients with advanced gastric cancer (GC). We performed a subgroup meta-analysis to identify specific GC patient subgroups that would derive survival benefit from ICIs. PD-L1 positivity was the only feature associated with a significant survival benefit from ICIs (interaction HR: 1.41, p 0.02). Numerically, the second most relevant interaction was ICI efficacy and gender, with ICI being more effective in males. Other molecular, biochemical and clinical features as potential predictors of efficacy are eagerly awaited. Abstract: Background: immune checkpoint inhibitors(ICIs) have shown contradictory results in patients with advanced gastro-oesophageal junction/gastric cancer(GOJ/GC). Aim: to identify specific patient subgroups that would derive survival benefit from ICIs. Methods: a subgroup meta-analysis of randomised clinical trials(RCTs) was carried out. Results: four phase-III-RCTs were identified with data on the following variables: primary location(Gastric vs GOJ); age(≤ 65 vs >65); gender(male vs female); ECOG PS(0 vs 1); ethnicity (Asian vs non-Asian), histology(intestinal vs diffuse), PD-L1 expression(≥ 1% vs < 1%). PD-L1 positivity was significantly associated with survival benefit from ICIs (HR: 0.82, p 0.047), with a significant interaction between PD-L1 expression and ICI efficacy (interaction HR: 1.41, p 0.02). Numerically, the second most relevant interaction was ICI efficacy and gender, with ICI being more effective in males. Conclusion: The PD-L1 positive patient subgroup derives significant survival benefit from ICI in GOJ/GC, however other predictors are eagerly needed to further refine patient selection.